Modern studies international issues - Cooney, Frank; Hughes, Gary; Kelly, Pauline; O'Reilly, Steph (Dynamic learning, 2020)
Exam Board: SQA Level: Higher Subject: Modern Studies First Teaching: August 2018 First Exam: June 2019 Updated specifically to match the SQA Higher Modern Studies syllabus for examination from 2019 onwards. International Issues covers three of the world powers that students may choose to study in this unit of the course (the United States of America, the Republic of South Africa and the People's Republic of China), along with Development Issues in Africa and Global Security.